Comparison of Patterns of Non-suicidal Self-Injury and Emotion Dysregulation Across Mood Disorder Subtypes - Yang, So Yung; Lee, Dongbin; Jeong, Hyewon; Cho, Yunji; Ahn, Jae Eun; Hong, Kyung Sue; Baek, Ji Hyun (Frontiers in Psychiatry, 2022)
Introduction: Non-suicidal self-injury (NSSI) is frequently encountered in patients with mood disorders. Emotion dysregulation (ED), frequently observed in mood disorders, could be a major mediating factor in NSSI. The aim of this study was to explore differences in NSSI behavior and ED across mood disorder subtypes. The relationships between childhood trauma and NSSI and ED were also explored. Methods: A total of 191 patients with mood disorders were included in this study. The patterns of NSSI behavior and ED across patients with bipolar I disorder (BD-I), bipolar II disorder (BD-II), and major depressive disorder (MDD) were compared. Results: More than half (54%) of the subjects experienced NSSI. Patients with BD-II and MDD engaged in NSSI behavior more frequently than those diagnosed with BD-I. NSSI behaviors in patients with BD-II most commonly included cutting, whereas hitting behaviors were most common among other groups. Patients with BD-II and MDD reported more severe ED than those with BD-I. In the case of childhood trauma, those with BD-II and MDD reported greater emotional neglect than those with BD-I. Structural equation modeling revealed that ED mediated the association between childhood trauma and NSSI. Conclusion: BD-I was associated with less frequent NSSI behavior and less severe ED than BD-II and MDD. ED mediated the association between childhood trauma and NSSI. Promoting emotion regulation strategies could prevent NSSI behavior in patients with mood disorders.